Avaliação da concentração sérica de substâncias antioxidantes em pacientes portadores de câncer de mama tratadas com doses nutraceuticas de glutamina : Ensaio clínico duplo cego randomizado - Farias, José Wilson Mourão de (2014)
To evaluate the effects of oral administration of GLN on the oxidative stress in women with breast cancer undergoing neoadjuvant FAC chemotherapy (5fluouracil 500mg/m2 + Doxorubicin50 mg/m2 + Cyclophosphamide 500 mg/m2 body surface area). METHODS: Twenty women (mean age: 51.7 years) with breast ductal carcinomas classified as T2b, T3a, T3b, T3c and all of T4 were included in the study, regardless of pre or post menopause status. Sachets containing glutamine 15g (“A”) or milk protein 15g (“B”) were prepared by a registered pharmacist. Allocation of patients was made by software program. Patients who received sachets labeled “A” were included in G1 group. The remaining patients, treated with the preparation labeled “B”, were included in group G2. Sachets contents were blended in 150 ml of drinking water, and were given daily to each patient during the entire course of neoadjuvant chemotherapy. Peripheral blood samples were collected in the first day of each of the three cycles of chemotherapy before drug infusion. Tumor and normal breast samples were collected at the end of Patey´s surgical procedure. Samples were analysed for GSH and TBARS contents. RESULTS: TBARS and GSH values were not different in breast healthy and tumor tissues nor blood when comparing control (G-2) and glutamine-treated (G-1) patients. Also, no significant differences were found in TBARS and GSH levels comparing different timepoints within the same group. CONCLUSION: Oral GLN (15gr/day) offers no protection against systemic or local oxidative stress in women with breast Ca undergoing neoadjuvant chemotherapy (FAC).